Exploring the Plant Growth-Promotion Properties of Rhizospheric and Endophytic Bacteria Associated with Robinia pseudoacacia L. in Serpentine Soil - Hasanović Mujo; Hrelja Emir; Hajro Anesa Ahatović; Murtić Senad; Durmić-Pašić Adaleta (Polish Journal of Microbiology, 2024)
Serpentine soils are characterized as a unique environment with low nutrient availability and high heavy metal concentrations, often hostile to many plant species. Even though these unfavorable conditions hinder the growth of various plants, particular vegetation with different adaptive mechanisms thrives undisturbed. One of the main contributors to serpentine adaptation represents serpentine bacteria with plant growth-promoting properties that assemble delicate interactions with serpentine plants. Robinia pseudoacacia L. is an invasive but adaptive species with phytoremediation potential and demonstrates extraordinary success in this environment. To explore more in-depth the role of plant growth-promoting serpentine bacteria, we isolated them and tested their various plant growth-promoting traits both from the rhizosphere and roots of R. pseudoacacia. Based on the demonstrated plant growth-promoting traits such as siderophore production, phosphate solubilization, nitrogen fixation, indole-3-acetic acid production, and ACC deaminase production, we sequenced overall 25 isolates, 14 from the rhizosphere and 11 from the roots. Although more efficient in exhibiting plant growthpromoting traits, rhizospheric bacteria showed a low rate of diversity in comparison to endophytic bacteria. The majority of the isolates from the rhizosphere belong to Pseudomonas, while isolates from the roots exhibited higher diversity with genera Pseudomonas, Bacillus, Staphylococcus, Lysinibacillus and Brevibacterium/Peribacillus/Bacillus. The capacity of the described bacteria to produce siderophores, solubilize phosphate, and fix nitrogen highlights their central role in enhancing nutrient availability and facilitating R. pseudoacacia adaptation to serpentine soils. The findings highlight the potential significance of serpentine bacteria, particularly Pseudomonas, in contributing to the resilience and growth of R. pseudoacacia in serpentine environments.